Association Between Glycated Hemoglobin (HbA1c) with Serum Cholesterol in Young Adults - Sugiarti, Mimi; -, hartanti; Sulistianingsih, Eka; -, Prasetyowati (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2025)
This research explores the potential association between glycated hemoglobin (HbA1c) and total serum cholesterol among early adults. Utilizing a cross-sectional analytic approach, the study recruited 72 students from four universities located in Bandar Lampung and Metro City, Lampung Province. Laboratory testing was conducted to assess cardiovascular risk through measurements of HbA1c and cholesterol levels. Pearson correlation analysis was applied to examine the relationship between the variables. The results revealed no statistically significant correlation between HbA1c and total cholesterol (r = 0.009, p = 0.9391), nor between HbA1c and blood pressure (r = 0.0118, p = 0.9213). Despite the absence of significant associations, these findings highlight the importance of early metabolic screening in young populations to support timely interventions and prevent long-term cardiovascular issues.